Impact of the maturation process on soot particle aggregation kinetics and morphology. (September 2021) - Morán, José; Henry, Christophe; Poux, Alexandre; Yon, Jérôme
Abstract: Mature soot aggregates exhibit a morphology which is currently mimicked by diffusion-limited aggregation (DLCA) codes, i.e. with a sticking probability = 1 when two aggregates collide. Nevertheless, nascent soot particles may grow in the reaction-limited aggregation regime (RLCA), i.e. with a sticking probability ≪ 1. Yet, it remains to be seen how fast the transition from RLCA to DLCA occurs for soot particles and what is the impact on aggregation kinetics, particle size distribution and morphology. This work intends to fill this gap by exploring the aggregation of soot particles formed in a laminar premixed flame through numerical simulations. Results show that the transition from RLCA to DLCA is very fast and produces a moderate impact on soot formation dynamics and morphology. However, soot particles mass bulk density is found to play an important role and should be considered in future simulations of soot formation in flames. Graphical abstract: Image 1 Highlights: Numerical study of the formation and evolution of soot aggregates in a flame. Collision and sticking probabilities evolving with maturity and electrostatics. Aggregate morphology characterized using Monte-Carlo Collision Algorithm. A sticking critical diameter around 10 nm is proposed. Soot mass bulk density evolution influences sot formation dynamics.